Influência de diferentes misturas em tanque contendo o herbicida 2,4-D no espectro de gotas da aplicação - Gandolfo, Ulisses Delvaz [UNESP] (2014)
The control of weed population is one of the major acts in a field installed crop, prevent ing the competit i on with nutrients, sunlight and water . The tank mixture of herbicides increase s the spectrum control of the application s , collaborating to reduction the processes of resistant plants selection or herbicides tolerant . In view of tho s e information , the aim of this work was study the influence of different tank mixtures containing the 2,4 - D in droplet spect rum of the application . The study was conducted at the Experimental Farm Lageado of the Faculdade de Ciências Agronômicas - UNESP , Botucatu - SP , in the Laboratory Machines f or Spraying of the Center Testing of Agricultural Machinery and T ires (NEMPA ), a nd Laboratory of Particle Size Analysis ( LAPAR ) , located in the Department of Plant Protection, FCAV / UNESP , Jaboticabal - SP. The treatments definition was made from the constitution of six spray solutions with the herbicide 2,4 - D (DMA 806 BR) isolated o r in tank mixture ...